Analisa Kapasitas Jalan Kawasan Perumahan BTP Akibat Parkir Pada Badan Jalan - Saputra, M. Indrawan; Yunus, Ahmad Yauri; Yunianti, Nurhadijah (Program Studi Teknik Sipil Universitas Bosowa, 2025)
The development of cities and the rapid growth of Indonesia's population have caused the traffic volume in Makassar City to continue to increase. As the provincial capital and center of economic, industrial, trade and educational activities in South Sulawesi, Makassar City is also the center of the traffic flow of goods and services from the surrounding area. The impact of the growth of trade and service centers that attract the movement of visitor vehicles is an increase in the need for parking spaces. This study aims to determine the impact of on-street parking on speed and traffic density on Jalan Tamalanrea Raya and to provide a basis for developing solutions. The survey was carried out for 3 days a week, 20 October – 24 October 2022. The location of the research object is located on Jalan Tamalanrea Raya, and volume, speed and parking data are collected from the main congestion points. The results showed that parking on the road causes the road capacity to decrease, with the lowest speed reaching 8.33 km/hour, the highest density reaching 144 vehicles/km, and the highest degree of saturation is 0.54 with service level C.